A flexible zinc tetrazolate framework exhibiting breathing behaviour on xenon adsorption and selective adsorption of xenon over other noble gases1. Issue 20 (28th May 2015) - Xiong, Shunshun; Liu, Qiang; Wang, Qian; Li, Wei; Tang, Yuanming; Wang, Xiaolin; Hu, Sheng; Chen, Banglin
<x xml:space="preserve">Abstract</x> We present a flexible zinc tetrazolate framework with breathing behaviour on Xe adsorption and significantly high Xe/Kr selectivity under flow condition.